The unusual case of child tantrum - a case report - Devaraj, Navin Kumar (Fortune Journals, 2019)
This is an amazing case report about an eight years old child that displayed child tantrum more synonym of the younger age group. This case also entails how the author managed to uncover the true reasons for his tantrum that left his guardian truly amazed at the ability of physicians to solve a seemingly difficult behavioural problem.